Viruses and phospholipids: Friends and foes during infection - Rattay, Stephanie; Hufbauer, Martin; Hoboth, Peter; Sztacho, Martin; Akgül, Baki (Journal of medical virology, 2023)
Viruses have evolved complex and dynamic interactions with their host cells to enable viral replication. In recent years, insights have been gained into the increasingly important role of the host cell lipidome in the life cycle of several viruses. In particular, viruses target phospholipid signaling, synthesis, and metabolism to remodel their host cells into an optimal environment for their replication cycle. Conversely, phospholipids and their associated regulatory enzymes can interfere with viral infection or replication. This review highlights examples of different viruses that illustrate the importance of these diverse virus-phospholipid interactions in different cellular compartments, particularly the role of nuclear phospholipids and their association with human papillomavirus (HPV)-mediated cancer development.
Keywords: fosfolipidy; viry; phospholipids; Host-Pathogen Interactions; Virus Diseases; virus host interactions; lidé; Phospholipids; replikace viru; Virus Replication; Viruses; interakce hostitele a patogenu; Humans; virus lipid interactions; virové nemoci